An optimised method for calculating the O+-O collision parameter from aeronomical measurements - Davis, C. J.; Farmer, A. D.; Aruliah, A. (Annales Geophysicae, 1995)
A study has been made of the interaction between the thermosphere and the ionosphere at high latitudes, with particular regard to the value of the O+-O collision parameter. The European incoherent scatter radar (EISCAT) was used to make tristatic measurements of plasma parameters at F-region altitudes while simultaneous measurements of the neutral wind were made by a Fabry-Perot interferometer (FPI). The radar data were used to derive the meridional neutral winds in a way similar to that used by previous authors. The accuracy of this technique at high latitudes is reduced by the dynamic nature of the auroral ionosphere and the presence of significant vertical winds. The derived winds were compared with the meridional winds measured by the FPI. For each night, the value of the O+-O collision parameter which produced the best agreement between the two data sets was found. The precision of the collision frequency found in this way depends on the accuracy of the data. The statistical method was critically examined in an attempt to account for the variability in the data sets. This study revealed that systematic errors in the data, if unaccounted for by the analysis, have a tendency to increase the value of the derived collision frequency. Previous analyses did not weight each data set in order to account for the quality of the data; an improved method of analysis is suggested.